2015
DOI: 10.1007/s12975-015-0429-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Focal Cerebral Ischemia on Exosomal Versus Serum miR126

Abstract: Emerging data suggest that exosomal microRNA (miRNA) may provide potential biomarkers in acute ischemic stroke. However, the effects of ischemia-reperfusion on total versus exosomal miRNA responses in circulating blood remain to be fully defined. Here, we quantified levels of miR-126 in whole serum versus exosomes extracted from serum and compared these temporal profiles against reperfusion and outcomes in a rat model of acute focal cerebral ischemia. First, in vitro experiments confirmed the vascular origin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Previous studies have reported that knockout of miR-126 induces cardiac dysfunction [38, 39]. MiR-126 expression level in circulation is an indicator of systemic inflammatory and angiogenic status [40, 41]. MiR-126 concentration in the circulation is significantly decreased in ischemic stroke [17] and acute myocardial infarction patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that knockout of miR-126 induces cardiac dysfunction [38, 39]. MiR-126 expression level in circulation is an indicator of systemic inflammatory and angiogenic status [40, 41]. MiR-126 concentration in the circulation is significantly decreased in ischemic stroke [17] and acute myocardial infarction patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, expression profiling of blood was conducted in parallel with brain (Liu et al, 2010; Jeyaseelan et al, 2008) and CSF (Sørensen et al, 2014) that showed overlapping patterns of miRNA levels between blood/brain and blood/CSF. The miRNAs that showed altered levels in blood after stroke include miR-107 (Yang et al, 2016b), miR-128b (Yang et al, 2016b), miR-153 (Yang et al, 2016b), miR-124 (Weng et al, 2011; Laterza et al, 2009), miR-210 (Zeng et al, 2011), miR-145 (Gan et al, 2012), miR-21 (Zhou and Zhang, 2014; Tsai et al, 2013), miR-221 (Tsai et al, 2013), miR-30a (Long et al, 2013), miR-126 (Chen et al, 2015a; Long et al, 2013), let-7b (Long et al, 2013), miR-223 (Wang et al, 2014d) and miR-24 (Zhou and Zhang., 2014). Importantly, Yang et al (2014) showed that miR-107 was elevated in the plasma of both rats and humans after stroke.…”
Section: Micrornas As Stroke Biomarkersmentioning
confidence: 99%
“…Studies have suggested a neuroprotective role of miR-29c 20 21. Serum miR-126 has been associated with the severity of cerebral ischemia and correlated with the extent of edema surrounding intracerebral hemorrhage 22 23. The overexpression of miR-126 may promote vascular integrity and protect the kidney from ischemic reperfusion injury 24.…”
Section: Discussionmentioning
confidence: 99%